“El Leasing como medio de financiamiento para las micro y pequeñas empresas y su aplicación contable” - Ramírez Leveaú, Miguel (2013)
At present, the Micro and Small Enterprises sector constitute more than 80% of the economic activity of the country, and as the main axis in the national production, they move a great amount of money in the financial market, using different sources of financing that they are provided by specialized entities in that sector. There are different options available to Micro and Small companies for their financing, in most cases these are used to solve the expansion of their operations or to invest in working capital. However, it is still observed that the entrepreneurs choose to reinvest their profits in the turn of the business, since there is still a certain distrust to acquire loans, because they are not informed about the existing financing modalities. In this sense, due to the importance of the micro and small business sector in the country's growth and development, it allows Leasing to be presented as a medium-term financing alternative that facilitates the acquisition of fixed assets without the need for liquidity, optimizing financial management and tributary of business. Thus, when conducting a leasing operation, the entrepreneur may record as depreciation the depreciation of the asset plus the financial interests; it can also accelerate the depreciation of the goods in a linear way until the term of the contract. In this report the definition, classification and accounting of the Leasing are in accordance with the criteria included in International Accounting Standard NIC17 Leases. Emphasis will be placed on the Financial Leasing because it is of greater application and will show practical cases for better understanding and proper accounting.